“Come and find your (love) story”. - Sabina Owsianowska (Via@)
It was not until the political transformation in Central and Eastern Europe in the 1990s that freedom, democratisation and new opportunities in travelling emerged. In connection with broader economic, social and cultural changes after the collapse of communism, tourism promotion acted in multiple ways; among them, modification of the decades-rooted image of the region – and particular countries – may be considered the key function. In this article, I propose reflection on what role in this process is played by references to the embodiment of tourist practices and performances, sensuality, love and eroticism, used by the senders of the message to reshape the image of Poland in selected promotional campaigns issued between 2004 and 2015. The main goal of this paper is not only to discuss the methods and techniques chosen by the broadcasters, but also to pay attention to the content that remains (un)intentionally ambiguous.